How does working time impact perceived mental disorders? New insights into the U-shaped relationship - Niu, Xiaoru; Li, Chao; Xia, Yuxin (Frontiers in Public Health, 2024)
Based on a large-scale nationally representative survey in China, this paper uses the exogenous impact of automation on working hours as the instrumental variable to examine working time's impact on perceived mental disorders, on the basis of dealing with endogeneity. Different from existing literature, it is found that the impact of working time on perceived mental disorders is Ushaped, rather than linear. Mental disorders firstly decrease with working hours. After working more than 48.688 hours per week, further increases in working time carry notable mental health costs, leading to a positive relationship between working hours and depression. The turning point of this Ushaped relationship is almost in line with the International Labour Organization's 48 working hours/week standard, justifying it from a mental health perspective. In addition, we further exclude the possibility of more complex nonlinear relationships between working time and perceived mental disorders. Furthermore, heterogeneities are found in the effects of working hours on mental disorders across different subgroups. Males are more depressed when working overtime. Older workers have a lower tolerance for overwork stress. The turning point is smaller for the highly educated group and they are more sensitive to working longer. Those with higher socioeconomic status are less depressed after exceeding the optimal hours of work. The increase in depression among rural workers faced with overwork is not prominent. Perceived mental disorders are lower among immigrants and those with higher health status. In addition, labor protection and social security help to weaken mental disorders caused by overtime work.